2012
DOI: 10.1177/1420326x12464507
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of fine particulate matters in the subway system of Istanbul

Abstract: The purpose of this study was to determine the concentrations of fine particulate matter (PM2.5) at six subway stations. The PM2.5 levels were compared at the platforms, inside the trains’ cabin and at the train driver’s cabin in the first section of the train. The measurements were grouped into three sections: (1) six underground platforms, (2) trains’ cabin and (3) train driver’s cabin in the Aksaray-Airport light metro line (M1) and the Taksim-4.Levent metro line (M2). On average, the highest PM2.5 concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 29 publications
2
29
0
Order By: Relevance
“…These transport types are of concerned for their risk of droplet transmission of infectious diseases. As in other studies; we observed that the PM2.5 concentrations experienced by commuters are much higher than concentrations measured at fixed monitoring stations [6,7,11]. In the previous study carried out in Avcılar-Istanbul, the daily average PM 2.5 concentration was determined as 39 µg/m3 at the fixed monitoring station [12].…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…These transport types are of concerned for their risk of droplet transmission of infectious diseases. As in other studies; we observed that the PM2.5 concentrations experienced by commuters are much higher than concentrations measured at fixed monitoring stations [6,7,11]. In the previous study carried out in Avcılar-Istanbul, the daily average PM 2.5 concentration was determined as 39 µg/m3 at the fixed monitoring station [12].…”
Section: Resultssupporting
confidence: 58%
“…Home to 16 million, Istanbul is Turkey's most populous city. Its' traffic is very congested, with registered vehicles numbering around 3.5 million [7]. The study area is located in Istanbul's European side between the districts of Avcılar and Bakırköy, which include dense commercial and residential areas.…”
Section: A Study Domainmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the lowest concentrations of PM in overhead carriages, there are still some cities where air quality exceeds standards. For example, studies found that PM 2.5 concentrations in ground train compartments reached 67 µg/m 3 in Istanbul [46].…”
Section: Driving Factors Of Subway Particulate Matter (Pms) Variationsmentioning
confidence: 99%
“…Fast ferry and car ferry are preferred on the routes that require long travelling time, because they offer more comfort and shorter commuting time in comparison to road transport. Several studies were carried out to determine the concentration of PM 10 , PM 2.5, and particle number in road transport vehicles [29,30] and in the subway [31,32] in Istanbul. This is the first comprehensive study conducted on personal exposure in marine transport where also the relationships between air pollutants and environmental factors are presented.…”
mentioning
confidence: 99%